Better Workers Move to Better Firms: A Simple Test to Identify Sorting - Cristian Bartolucci; Francesco Devicienti (Institute for the Study of Labor (IZA), 2013)
We propose a simple test that uses information on workers' mobility, wages and firms' profits to identify the sign and strength of assortative matching. The basic intuition underlying our empirical strategy is that, in the presence of positive (negative) assortative matching, good workers are more (less) likely to move to better firms than bad workers. Assuming that agents' payoffs are increasing in their own types, our test exploits within-firm variation on wages to rank workers by their types and firm profits to rank firms. We use a panel data set that combines social security earnings records for workers in the Veneto region of Italy with detailed balance-sheet data for firms. We find robust evidence that positive assortative matching is pervasive in the labor market. This result is in contrast with what we find from correlating the worker and firm fixed effects in standard Mincerian wage equations.
Keywords: J6; J31; L2; 330; assortative matching; worker mobility; wages; profits; matched employer-employee data